Quyền kiểm soát công ty mục tiêu và chênh lệch giá trong hoạt động mua lại và sáp nhập tại Việt Nam - Hồ Hồng Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This study is one of the first studies which evaluates the impact of the acquirer’s control motive on M&A premium in Vietnamese stock market. Using a combination of impact analysis of an event and multivariate regression upon M&A data in the 2007–2016 period, this paper finds the strong motivation for control rights, rather than the financial gains, in M&A transactions. Such finding is more consistent with the theory of the market for corporate control than the theory on the motivation for financial gain via M&A transactions.